2022
DOI: 10.1136/annrheumdis-2022-eular.3561
|View full text |Cite
|
Sign up to set email alerts
|

Ab0988 frequency of Osteopenic Syndrome and Low-Energy Fractures in Postmenopausal Women With Osteoarthritis of the Knee Joint

Abstract: BackgroundThe impact of knee osteoarthritis on the risk of low-energy fractures remains an open question in recent times. Some cohort studies show that OА of the knee joint is associated with increased risk of fractures [1-3]. Other studies do not support this link [4-5].Objectivesto compare the incidence of osteopenic syndrome and low-energy fractures in postmenopausal women with osteoarthritis (OA) of the knee joint.MethodsThe study includes 98 women, of whom: 51 (median age 63.0 [59.3;69.8] years) are diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ICD-9) [ 40 ]. Fractures were self-reported in 5 studies [ 16 , 19 , 39 , 41 , 42 ], and the remaining were based on medical records (i.e. hospital database, ICD-10 or ICD-9) [ 14 , 17 , 18 , 37 , 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICD-9) [ 40 ]. Fractures were self-reported in 5 studies [ 16 , 19 , 39 , 41 , 42 ], and the remaining were based on medical records (i.e. hospital database, ICD-10 or ICD-9) [ 14 , 17 , 18 , 37 , 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported both non-vertebral and vertebral fractures. One study was not evaluated for NOS score because it is a conference abstract [ 39 ]. Two studies had NOS scores of < 7 and were considered to have a high risk of bias (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%